Design, Simulation and Hardware Implementation of a Multi Device Interleaved Boost Converter for Fuel Cell Applications - R. Seyezhai (Institute of Advanced Engineering and Science, 2014)
This paper presents the analysis and implementation of a two-phase Multi Device Interleaved Boost Converter (MDIBC). Among the various DC-DC topologies, Multi device Interleaved converter is considered as a better solution for fuel cell hybrid vehicles as it reduces the input current ripple, output voltage ripple and the size of passive components. Detailed analysis has been done to investigate the benefits of Multi device Interleaved boost converter by comparing it with the conventional Interleaved boost converter topology. Moreover, in this paper, power loss analysis (switching loss, conduction loss, inductor loss) of the proposed converter has been performed. Simulation study of Multi device interleaved converter has been studied using MATLAB/SIMULINK. Hardware prototype is built to validate the results.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5883